The influence of nutrient media modification on the morphological parameters in raspberry (Rubus idaeus L.) micropropagation in the liquid and semi-solid media - Bošnjak, Dejan; Marković, Monika; Agić, Dejan; Vinković, Tomislav, agronom; Tkalec Kojić, Monika; Ravnjak, Boris; Stanisavljević, Aleksandar, agronom (2021)
Within the nursery sector, a global interest in functional fruits imposes a permanent need to improve the tissue culture technology. A modern bioreactor immersion system is currently a valid solution for the micropropagation of many cultures. At the Faculty of Agrobiotechnical Sciences Osijek (FAZOS, Croatia), a research was conducted with the aim of improving the raspberry (Rubus idaeus L., cv. HimboTop®) micropropagation protocol. The treatments implied the modifications of the MS and DKW nutrient medium (DKW – standard; DKWm – substitution of FeEDTA with the FeEDDHA; MSm – macroelement modification, 3 x CaCl2, MgSO4, and KH2PO4 + FeEDDHA), differently depending on the aggregate condition (semi‐solid and liquid SETISTM). Subsequent to 15 (SETISTM) and 30 cultivation days (semi-solid medium), respectively, a morphological parameter analysis and a multiplication success evaluation were commenced. In all treatments (DKW, DKWm, and MSm), the observed parameters (shoot height, number of leaves, leaf width and length) were significantly better in an interaction with the liquid medium. Comparing the models, a liquid medium (SETISTM) resulted in a significantly higher explant multiplication (4.02) (a semi‐solid medium - 2.74). The best reproduction quality, implying a better plant vigor with a reduced vitrification, was obtained on the MSm medium in the SETISTM. A concentration optimization of individual mesocomponents (i.e., of the macroelements) and their chemical forms (FeEDDHA) may contribute to their improved adoption and consequently to the stress suppression due to an explant transplantation. Selecting the modern technical solutions (TIS bioreactors - SETISTM) and continuously improving the protocols, we may obtain the realistically sustainable models, suitable for a massive clonal reproduction.
Globalni interes za funkcionalnim voćem u rasadničarskom sektoru nameće permanentnu potrebu usavršavanja tehnologije kulture tkiva. Suvremeni imerzni sustav bioreaktora trenutno predstavlja validno rješenje za mikropropagaciju brojnih kultura. Pri Fakultetu agrobiotehničkih znanosti Osijek (FAZOS, Hrvatska) provedeno je istraživanje s ciljem usavršavanja protokola za mikropropagaciju maline (Rubus idaeus L.) kultivar HimboTop®. Tretmani su uključivali modifikacije hranjivog medija Murashige i Skoog te Driver i Kuniyuki (DKW - standard; DKWm - supstitucija FeEDTA sa FeEDDHA; MSm - modifikacija makro elemenata 3 x CaCl2, MgSO4 i KH2PO4 + FeEDDHA), različitih obzirom na agregatno stanje (polučvrsti i tekući SETISTM). Nakon 15 dana (SETISTM) i 30 dana (polučvrsti medij) kultivacije izvršena je analiza morfoloških parametara te evaluacija uspješnosti multiplikacije. Na svim tretmanima (DKW, DKWm, MSm) promatrani parametri (dužina izdanka, broj izdanaka, broj listova, širina lista, dužina lista) bili su značajno bolji u interakciji sa tekućim medijem. Usporedbom modela, tekući medij (SETISTM) rezultirao je značajno većom multiplikacijom (4,02) eksplantata u odnosu na polučvrsti medij (2,74). Najbolja kvaliteta reprodukcije, uključujući bolji vigor biljke uz smanjenu vitrifikaciju, postignuta je na MSm mediju u SETISTM. Optimizacija koncentracije pojedinih mezokomponenti makro elemenata i njihovih kemijskih oblika može doprinijeti poboljšanom usvajanju istih te posljedično prevladavanju stresa uslijed transplantacije eksplantata. Odabirom suvremenih tehničkih rješenja (TIS bioreaktori - SETISTM) i kontinuiranim usavršavanjem protokola moguće je dobiti realno održive modele pogodne za masovnu klonsku reprodukciju.
Bibliografija: 33 jed.
Summary ; Sažetak.
Keywords: Malina -- Mikropropagacija -- Optimizacija medija -- Bioreaktor